1992
DOI: 10.1016/0014-5793(92)81315-d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for new phosphorylation sites for protein kinase C and cyclic AMP‐dependent protein kinase in bovine heart 6‐phosphofructo‐2‐kinase/fructose‐2,6‐bisphosphatase

Abstract: Bovine heart 6.phosphofructo-2-kinase/fructosL h-2b-bisphosphatasc (PFK-2/FBPase-2) was phosphorylated by incubation with [r-'rP]MgATP and cyclic AMP-dependent protein kinasc (PKA) or protein kinasc C (PKC). After digestion with chymotrypsin, the phosphorylation sites for the two protein kinascs were identified by pcpddc mapping, and microsequencing. Evidence for new phosphorylation sites for PICA (Ser-483) and PKC (Ser.84 and Ser-466) was obtained.6-Phospliofructo-2-kinas~fructose-2,G-bisphospl~atasc; Phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…Thus, the H54 isoform lacks all these sites although it still shares with the H59, H60 and H61 isoforms SerR4, which is phosphorylated by PKC [7]. The difference in C-terminal sequences also bears on the overall subunit charge (see above), which is liable to change upon phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the H54 isoform lacks all these sites although it still shares with the H59, H60 and H61 isoforms SerR4, which is phosphorylated by PKC [7]. The difference in C-terminal sequences also bears on the overall subunit charge (see above), which is liable to change upon phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, exon 15 codes for Ser466 which is phosphorylated by PKA and PKC, for Thr4" which is phosphorylated by PKC, and for Ser483 which is phosphorylated by PKA [7,8,11]. Thus, the H54 isoform lacks all these sites although it still shares with the H59, H60 and H61 isoforms SerR4, which is phosphorylated by PKC [7].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphopeptides were identified in MS 2 mode by the loss of H 3 PO 4 (98 Da) under low collision-induced dissociation energy, and the phosphorylated residue was pinpointed in MS 3 mode. In some cases, radioactive peaks were further purified for Edman sequencing (30).…”
Section: Methodsmentioning
confidence: 99%
“…The final incubation volumes were 0.15 ml for PKA, p70 s6k , and MAPKAP kinase-1 and 0.3 ml for PKB. After 2 h at 30°C, protein was precipitated (17) and digested in 0.2 ml of 0.1 M Tris-Cl, pH 8.6, and 2 M urea with 1 g of bovine trypsin overnight at 30°C. Peptides were separated by narrow bore HPLC (15), collected by hand in Eppendorf tubes, and counted by Cerenkov radiation.…”
Section: Methodsmentioning
confidence: 99%
“…In bovine heart, two alternatively spliced forms have been described (15,16), migrating with M r values of 58,000 and 54,000 on SDS-polyacrylamide gels (15). Peptide sequence analysis revealed that the M r 54,000 form lacks phosphorylation sites for PKA (Ser-466 and Ser-483) and protein kinase C (Ser-466 and Thr-475), which are encoded by exon 15 and thus present in the M r 58,000 form (15,17). The situation in bovine heart is further complicated by the fact that four different mRNAs have been characterized (18).…”
mentioning
confidence: 99%